Karakteristik Manajemen Kepemimpinan dalam Sudut Pandang Islam - Maya Sri Rahayu; Sri Aisyah Amini; Yuniarti Yuniarti; Demina Demina (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
Stimulus for someone who wants to be involved to take part in a leadership process varies. The diversity of desires or motivations and the background of one's intention to be involved in becoming a leader is a passion that cannot be prevented and legalized by law because by nature humans are caliphs on earth. The attitudes and characteristics that must be possessed by a leader are: Shidiq (honest), Trustworthy, not deceiving, keeping promises, generous, and not forgetting the hereafter. Leadership is very important for the success of an organization and the management of other people. In general, the concept of management is an activity that seeks to achieve certain goals or objectives by utilizing other people (getting things done through the efforts of other people). The approach used in this discussion is a literature study that collects information and data from various existing sources. Effective leadership is used according to the people it leads (circumstances and situations). An Islamic leader must have Islamic character and qualified abilities including: leadership skills in supervising and controlling his people, the ability to plan and solve problems, be full of responsibility and have social skills and have the knowledge and professional competence of members and followers.